2021
DOI: 10.25095/mufad.842340
|View full text |Cite
|
Sign up to set email alerts
|

Faaliyet Kaldıracının Finansal Performans Üzerindeki Etkisini Belirlemede Satış Büyümesinin Rolü: Türkiye Örneği

Abstract: This article analyses the impact of sales growth on the association between operating leverage and financial performance. Using a sample of 200 firms listed on Istanbul Stock Exchange over the period from 2008 to 2017, we find that operating leverage has a negative effect on profitability, and that the negative effect of operating leverage is stronger (weaker) for firms with low (high) sales growth. It implies that sales growth mitigates the negative impact of operating leverage on profitability. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…In France, the CAPRAT ratio was seen to have a positive and statistically significant impact on the ROA of the firms, and the results are the same as the findings obtained from a Turkish study [24]. In both countries, the results showed that the DEEUTY ratio and LTTTTA that deviated from the golden ratio had a negative and significant impact on ROA, and the results are consistent with the findings obtained by the following researchers [84][85][86].…”
Section: The Impact Of a Golden Ratio-based Capital Structure On Epssupporting
confidence: 88%
See 2 more Smart Citations
“…In France, the CAPRAT ratio was seen to have a positive and statistically significant impact on the ROA of the firms, and the results are the same as the findings obtained from a Turkish study [24]. In both countries, the results showed that the DEEUTY ratio and LTTTTA that deviated from the golden ratio had a negative and significant impact on ROA, and the results are consistent with the findings obtained by the following researchers [84][85][86].…”
Section: The Impact Of a Golden Ratio-based Capital Structure On Epssupporting
confidence: 88%
“…Numerous investigatio formance [22][23][24][25]. A study o covered that short-term de ROA, ROE, and EPS but has that long-term debt to total c and ROE, while a negative a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afolabi et al (2019) found that sales growth has a positive and statistically significant effect on ROCE, which is commensurate with the study's findings. A study by Mamaro and Legotlo (2021) and Kalash and Bilen (2021) found that the size of the firms has a positive and significant effect on ROE, and the findings are commensurate with the study results.…”
Section: Financial Leverage and Financial Performancesupporting
confidence: 87%